1996
DOI: 10.1021/ic960791z
|View full text |Cite
|
Sign up to set email alerts
|

Iso- and Homeostructuralism of Analogous Ph4E and Ph3E−E‘R3 Compounds (E = C, Si, Ge, Sn, Pb; E‘ = Si, Ge, Sn; R = Me, Ph):  Crystal Structure of 1,1,1-Trimethyltriphenyldistannane

Abstract: The Ph3E−E‘Me3 (E = Si, Ge, Sn; E‘ = Si, Ge, Sn) compounds exhibit two morphotropic steps in the crystalline state:  a [E = E‘ = Si; E = Si, E‘ = Ge; E = Ge, E‘ = Si, E = E‘ = Ge (space group P3̄)] → b [E = Ge, E‘ = Sn; E = Sn, E‘ = Ge (space group Pna21)] → c [E = E‘ = Sn (space group P3̄)]. Ph3Sn−SnMe3 reverts to group a. Due to the long Sn−Sn bond, it is not isometric, and therefore not isostructural, with the group a compounds; the relaxed relationship is termed as homeostructural.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In the former case, the Me 3 E-E 0 Ph 3 dumbbells related by a center of symmetry are antiparallel, whereas in the orthorhombic pair of structures they are stacked in a parallel array. Continuing these investigations, we found that the crystals of Me 3 Ge-GePh 3 (Pá rká nyi et al, 1994), Me 3 Sn-SnPh 3 (Pá rká nyi et al, 1996) and some others, such as Me 3 Pb-SnPh 3 and Me 3 Pb-PbPh 3 (Preut & Huber, 1976), are again trigonal with the space group P " 3 3. A 180 rotation of the R 3 Ge-SnR 0 3 dumbbells, perpendicular to the respective E-E 0 bond, was attributed (Ká lmá n & Pá rká nyi, 1997) to the 0.19 Å difference in the covalent radii of Ge and Sn with respect to those of 0.11 and 0.06 Å observed between the Ge-Si and Pb-Sn pairs, respectively.…”
Section: Introductionsupporting
confidence: 58%
“…In the former case, the Me 3 E-E 0 Ph 3 dumbbells related by a center of symmetry are antiparallel, whereas in the orthorhombic pair of structures they are stacked in a parallel array. Continuing these investigations, we found that the crystals of Me 3 Ge-GePh 3 (Pá rká nyi et al, 1994), Me 3 Sn-SnPh 3 (Pá rká nyi et al, 1996) and some others, such as Me 3 Pb-SnPh 3 and Me 3 Pb-PbPh 3 (Preut & Huber, 1976), are again trigonal with the space group P " 3 3. A 180 rotation of the R 3 Ge-SnR 0 3 dumbbells, perpendicular to the respective E-E 0 bond, was attributed (Ká lmá n & Pá rká nyi, 1997) to the 0.19 Å difference in the covalent radii of Ge and Sn with respect to those of 0.11 and 0.06 Å observed between the Ge-Si and Pb-Sn pairs, respectively.…”
Section: Introductionsupporting
confidence: 58%
“…Comparison of the Sn-C and Sn-Sn bond lengths in 2 with those observed in other sterically crowded molecules shows that they display some, but not an excessive, elongation. For instance, comparison of the Sn-C distances for the tin methyl groups in Me 3 SnSnPh 3 (Sn-C(Me) ) 2.138(5) Å), 17 shows that they are ca. 0.03 Å shorter than the Sn-C(Me) bonds (ca.…”
Section: Resultsmentioning
confidence: 99%
“…The first has two RCOO" groups in a syn-syn arrangement bridging a pair of SnC 2 moieties [3][4][5][6]8]. The third group has no bridging ligands [9,11,[13][14][15]18,19,21,22,24,28], The third group has no bridging ligands [9,11,[13][14][15]18,19,21,22,24,28],…”
Section: Dimers Containing a Tin-tin Bondmentioning
confidence: 99%
“…In the third group of Sn 2 +6 derivatives, there are several examples with two tetrahedral tin atoms held together by a direct Sn-Sn bond; SnC 3 [9,11,[13][14][15]18,22,24,28], SnC 2 CI [13,22] and SnC 2 Br [18,21]. In another example [18a] two trigonal-bipyramidal units, SnC 2 NCI are linked, and overall the range of values for the Sn-Sn bond are from 275.9(4) to 303.…”
Section: Fig 1 Structure Of Sn 2^-ac) 2 (Ph) 4 [3] Fig 2 Structurmentioning
confidence: 99%